Effect of parent support on engagement through need satisfaction and academic buoyancy - ROHINSA, M.; CAHYADI, S.; DJUNAIDI, A.; ZULRIZKA ISKANDAR, T.B. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study is to test the model of the influence of support from parents on engagement through basic psychological needs satisfaction on middle school students. Participants in this study were 1352 students. The hypothesized model demonstrated a good fit with the data (RMSEA = .058; CFI = .993; NFI = .991; GFI = .961). It can be concluded that engagement can be formed by parents’ support through the mediation of internal processes within students. The findings reinforce the importance of the role of parents as part of the social context to fulfil basic psychological needs.RESUMEN El propósito de este estudio es probar el modelo de la influencia del apoyo de los padres en el compromiso a través de la satisfacción de las necesidades psicológicas básicas en los estudiantes de secundaria. Los participantes en este estudio fueron 1352 estudiantes. El modelo hipotético demostró un buen ajuste con los datos (RMSEA = .058; CFI = .993; NFI = .991; GFI = .961). Se puede concluir que la participación se puede formar dentro de los estudiantes. Los resultados refuerzan la importancia del papel de los padres como parte del contexto social para satisfacer las necesidades psicológicas básicas.